Research on the development of the meat processing industry as a component of Ukraine's food security - Olena Bochko; Nataliia Kosar; Nataliia Kuzo (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 15th Edition, 2024)
The meat processing industry is strategically important for ensuring Ukraine's food security, as its products are essential in every person's diet, contributing to proper health. Therefore, it is important to examine its current state both through statistical data and by gathering and analyzing primary marketing information. The collected and analyzed secondary marketing information indicates a decline in beef and veal production in Ukraine, which are considered the most beneficial meats for human health. At the same time, research shows that the import of sausages to Ukraine increased significantly during 2021-2022, with a slight decrease in 2023. This suggests an insufficient level of demand satisfaction for sausage products from domestic producers, which negatively impacts food security in Ukraine. Given the low per capita meat consumption and the importance of this product in supporting the normal functioning of Ukrainians, meat processing enterprises should actively promote increased meat and meat product consumption among the Ukrainian population, offering new products in the market that align with consumer preferences. Moreover, domestic meat processing enterprises should pay considerable attention to the quality parameters of their offered products, increase the use of beef and veal, which are considered healthier, and employ eco-friendly packaging, as many consumers prefer to purchase packaged meat and sausage products.
Keywords: D13; E37; F17; 330; food security; meat processing industry; eco-friendly packaging; sausage production and import; product quality